THOUGHT PATTERNS REFLECTED IN THE LINGUISTIC FEATURES IN INDONESIAN AND ENGLISH LETTERS WRITTEN BY INDONESIANS - Eddy Subandrijo; Susilo Susilo (TEFLIN, 2007)
This is a report of a qualitative study on contrastive thought patterns of Indonesian bilingual writers. The data are the thought patterns reflected in the linguistic features in English and Indonesian letters. The results reveal that rhetorical organizations developed and organized in both letters are similar in three ways. The paragraphs in both letters indicate similarities in terms of coherence. Three ways of sentence construction are found; four different shifts in grammatical style are made by the writers. The diction shows that for the English letters, in addition to using the colloquial lexemes, two kinds of lexemes are found: (a) jargon, and (b) attitudinal. For the Indonesian letters, three kinds of lexemes are found: (a) jargon, (b) attitudinal, (c) for-mality. In general, the results show that a large number of Indonesian letters follow quasi-linear thought patterns (QL), while a small number still follow the non-linear thought patterns (NL). For the English letters, the results reveal that the most percentage is converged on the line of category linear (L); less percentage is on category QL.